ANALISIS PENGARUH TRADE OPENNESS TERHADAP GROSS DOMESTIC PRODUCT ASEAN-5 PERIODE 2005-2014 - Soraya Nabila Putri; Suyanto Suyanto; Firman Rosjadi Djoemadi (Perpustakaan Universitas Surabaya, 2018)
This study aims to analyze the effect of trade openness, human development index, and foreign direct investment on gross domestic product in ASEAN-5 countries (Indonesia, Thailand, Singapore, Malaysia and Philippines) for 2005-2014 period. This research uses quantitative approach with panel data regression model. The results of this study indicate that trade openness has a significant positive effect on gross domestic product at quadratic level. Similarly, human development index and foreign direct investment individually have a statistically significant effect on gross domestic product. So it can be concluded that internal and external variables of ASEAN-5 countries have a positive and significant influence on gross domestic product.